The Political Economy of Conflict in Plateau State, 1994-2012 - UMOH, Anthony Imeh; NWINKOL , Barinaadaa (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
Conflict anywhere in the world operates through a distinct modus operandi, with its patterns shaping the political economy. The political, economic, social, and environmental forces unique to the region deeply influence the dynamics of conflicts in the Jos Plateau and its surrounding areas. Due to its strategic position as the capital of Nigeria's North Central region, rich deposits of tin ore, and temperate climate, Jos has historically attracted a diverse influx of migrants from various parts of the country, both during the colonial era and in contemporary times. This paper critically analyses the political economy of conflict in Jos and other parts of Plateau State using philosophical, critical, and textual analysis methods. It examines the intricate interplay between state and federal governments, conflict patrons, and non-state actors. Through a rigorous examination of the underlying texts and contexts, the study reveals that while the economy itself did not directly cause the conflict, the mechanisms of conflict—centred on arms proliferation, violence, and crime—are intricately linked to communal and ethnic tensions. The paper highlights how the manipulation of ethno-regional and ethno-religious dynamics in political and economic activities serves to perpetuate, rather than mitigate, conflict in the state. The study employs critical analysis to dissect how these dynamics weave into conflict, highlighting their role in intensifying tensions. Furthermore, textual analysis allows for a deeper understanding of the narratives and discourses that sustain these conflicts. The paper concludes that addressing these conflict drivers could have prevented or significantly mitigated the resurgence of conflicts in Plateau State during the period under review. By unpacking the philosophical underpinnings of these conflicts, this study provides a nuanced understanding of their persistence and suggests pathways for more effective conflict resolution strategies.